ASUHAN KEBIDANAN PADA BAYI Ny. Y DENGAN MELAKUKAN PENCEGAHAN INFEKSI PADA TALI PUSAT MENGGUNAKAN METODE TOPIKAL ASI - Pratiwi Dwi Handayani; Devy Lestari Nurul Aulia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
According to the World Health Organization (WHO) in 2017 found an infant mortality rate of 560,000 from live births caused by umbilical cord infection. The incidence of newborn infection in Indonesia ranges from 24% to 34%, and this is the cause of neonatal death which ranges from 24% to 34%, and this is the second cause of death after neonatal asphyxia which ranges from 49% to 60%. One way to treat the umbilical cord is the topical breastfeeding method. Breast milk has many immunological and anti-infective agents. The purpose of writing is to provide midwifery care for newborns by applying the topical breastfeeding method as a prevention of infection and to accelerate the release of the umbilical cord in Baby Ny. Y AT the Tanjung Balai Karimun Health Center. The design of care that has been given by the author is using a descriptive observational design with a case study approach. Data collection methods are participatory observation, interviews, measurements, documentation. The research instrument is the format of midwifery care. The results of the action showed that the treatment of the umbilical cord using topical breast milk made the umbilical cord dry and detached faster. It is hoped that the role of midwives in assisting mothers in caring for the umbilical cord in newborns is as a facilitator and counselor